2023
DOI: 10.2106/jbjs.22.00500
|View full text |Cite
|
Sign up to set email alerts
|

Radiographic Predictors of Conversion to Total Knee Arthroplasty After Tibial Plateau Fracture Surgery

Abstract: Background: Radiographic measurements of initial displacement of tibial plateau fractures and of postoperative reduction are used to determine treatment strategy and prognosis. We assessed the association between radiographic measurements and the risk of conversion to total knee arthroplasty (TKA) at the time of follow-up. Methods: A total of 862 patients surgically treated for tibial plateau fractures between 2003 and 2018 were eligible for this multic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 27 publications
0
2
0
Order By: Relevance
“…Our study revealed that a lateral articular surface depression depth ≥10.6 mm was associated with the use of dual incisions to obtain reduction. The importance of achieving adequate articular reduction is supported by a recent multicenter study by Assink et al 30 evaluating 477 tibial plateau fractures at 6.5-year average follow-up, showed that patients with residual articular incongruency 4.0–6.0 mm and ≥6.0 mm were 2.7x and 5.0x more likely, respectively, to undergo conversion to total knee arthroplasty. In planning articular reduction, surgeons may choose to use dual incisions in cases of increased depth of lateral articular surface depression.…”
Section: Discussionmentioning
confidence: 99%
“…Our study revealed that a lateral articular surface depression depth ≥10.6 mm was associated with the use of dual incisions to obtain reduction. The importance of achieving adequate articular reduction is supported by a recent multicenter study by Assink et al 30 evaluating 477 tibial plateau fractures at 6.5-year average follow-up, showed that patients with residual articular incongruency 4.0–6.0 mm and ≥6.0 mm were 2.7x and 5.0x more likely, respectively, to undergo conversion to total knee arthroplasty. In planning articular reduction, surgeons may choose to use dual incisions in cases of increased depth of lateral articular surface depression.…”
Section: Discussionmentioning
confidence: 99%
“…The observers consisted of an attending orthopaedic trauma surgeon (> ten years of experience) and technical physician (> five years of experience). CT scans were assessed in the axial, sagittal, and coronal planes to measure the initial displacement in terms of gap and step-off according to previously described methods, 11,12 and to determine the fracture classification according to the AO/OTA classification system. 13 Patient characteristics were retrieved from the electronical patient file.…”
Section: Methodsmentioning
confidence: 99%
“…Poor articular reduction and tibial alignment are associated with worse functional outcome [ 15 , 16 , 17 ]. In order to correct for the quality of the reduction in patients without a postoperative CT scan, the quality of the fracture reduction and the tibial alignment were evaluated on the postoperative radiographs using three radiographic parameters: articular fracture reduction, coronal alignment, and sagittal alignment.…”
Section: Methodsmentioning
confidence: 99%